Solid electrolyte for ammonia gas detection, electrochemical luminescence sensor, preparation method and detection method

An electrochemiluminescence sensor that uses a solid electrolyte to cover screen-printed electrodes, combined with cyclic voltammetry and potentiostatic-luminescence technology, solves the problems of time-consuming and invasive traditional blood testing, and achieves high sensitivity and high specificity detection of ammonia.

CN121253631APending Publication Date: 2026-01-02CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH

Patent Information

Application Number
CN202511828751.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-05
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Traditional blood tests for ammonia are time-consuming and invasive. Existing gas sensing technologies lack sufficient sensitivity and specificity in ammonia detection, making it difficult to achieve efficient and accurate ammonia detection.

Method used

Employing a solid-state electrolyte and an electrochemiluminescence sensor, a screen-printed electrode is covered with a Nafion/IL/PVDF/Ru(bpy)32+ electrolyte. Combining cyclic voltammetry and potentiostatic-luminescence technology, a highly sensitive ppb-level detection of ammonia is achieved.

Benefits of technology

It achieves selective detection of ammonia at ppb level with high sensitivity, wide linear response range and low detection limit at room temperature, and is suitable for high sensitivity and high specificity identification of exhaled ammonia.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121253631A_ABST
    Figure CN121253631A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sensors, and discloses a solid electrolyte for ammonia gas detection, an electrochemical luminescence sensor, a preparation method and a detection method, and the solid electrolyte for ammonia gas detection comprises the following raw materials: a second electrolyte, a luminescent substance, an optional first electrolyte and an optional binder. The solid electrolyte for ammonia gas detection provided by the invention can realize ppb-level NH3 selective detection with high sensitivity, wide linear response range and low detection limit at room temperature for an electrochemical luminescence sensor for detecting ammonia gas. The electrochemical luminescence sensor for detecting the ammonia gas can be used for sensing the ammonia gas through a cyclic voltammetry method and a constant potential-luminescence technology, and ppb-level high-sensitivity and high-selectivity ammonia gas detection is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of sensors, and particularly relates to a solid-state electrolyte for ammonia detection, an electrochemiluminescence sensor, a preparation method and a detection method. BACKGROUND

[0002] Ammonia (NH3) is an environmental pollutant and is highly toxic and corrosive to the skin, eyes and lungs of the human body, which can cause life-threatening diseases. In addition, ammonia is also a biomarker of liver and kidney disease. When the liver and kidney function metabolism is abnormal, ammonia cannot be effectively converted and accumulates in the body, resulting in significantly higher ammonia levels in the blood and exhaled breath of patients than in healthy people. The ammonia concentration in the exhaled breath of patients is usually 0.8-15 ppm, while that of healthy people is only 0.05-1.8 ppm. Traditional blood detection methods are not only time-consuming but also invasive, so there is an urgent need to develop efficient and accurate breath ammonia detection sensors to replace traditional blood detection. For human breath detection, there are two major characteristics: the concentration of ammonia is very low and the composition of breath is complex. Therefore, achieving high-sensitivity sensing and high-specificity recognition detection of ammonia still faces major challenges.

[0003] Electrochemiluminescence (ECL), also known as electrogenerated chemiluminescence, is essentially a type of luminescence based on electrochemical reactions. ECL signals are usually generated by luminophores through electron transfer processes in electrochemical reactions, completely based on electrochemical reactions occurring near the electrode surface, and can be simply controlled in time and luminescence processes by switching the applied potential, without the need for an independent light source, which can prevent problems such as scattered light in luminescence phenomena, and has unique advantages over photoluminescence (PL) and chemiluminescence (CL). With its high sensitivity, precision and minimal background interference, it is often used for the detection of biological signaling molecules. There have been many related research works, such as the detection of glucose and dopamine, usually the luminophore is connected with enzyme or catalyst, and tri-n-propylamine is generally used as a co-reactant for electrochemiluminescence sensing. For luminophores, tris (2, 2-bipyridine) ruthenium (II) (Ru(bpy)3 2+) is one of the most studied and utilized luminophores due to its high sensitivity and good regeneration ability in ECL process. Electrochemiluminescence sensor is a process that uses cyclic voltammetry (CV) to produce substances (luminophores and co-reactants) on the electrode surface to form an excited state of luminescence. Specifically, the electrochemiluminescence process has several steps: 1. The redox reaction of the luminophore and the co-reactant under the cyclic potential generates the intermediate substances of the luminophore and the co-reactant; 2. The reaction of the two intermediate substances generates the excited state of the luminophore; 3. The excited state of the luminophore emits light to return to the ground state and emit photons to produce a light signal. However, electrochemiluminescence technology is rarely recorded in gas environment-oriented sensing analysis. At present, potentiostatic-luminescence technology has not been developed in gas sensing detection.

[0004] Therefore, the prior art still needs to be improved and developed. SUMMARY

[0005] In view of the deficiencies of the prior art described above, the purpose of the present application is to provide a solid-state electrolyte, an electrochemiluminescence sensor, a preparation method and a detection method for ammonia detection, aiming to solve the problem of time-consuming and invasive detection of ammonia by traditional blood detection.

[0006] The technical solution of the present application is as follows: A solid-state electrolyte for ammonia detection, wherein the raw materials thereof include a second electrolyte, a luminophore, an optional first electrolyte and an optional binder; The volume ratio between the first electrolyte and the second electrolyte is 0-50:1-50; the mass ratio between the luminophore and the binder is 0.1-100:0-2500; 1-1000 mg of the luminophore is added per 100-5000 μL of the second electrolyte; The first electrolyte is a solution of a proton exchange membrane, which has high proton conductivity and includes but is not limited to one or a combination of two or more of SPEEK, PBI, heteropoly acid, Nafion and inorganic composite membrane; The second electrolyte is an ionic liquid, which has high ionic conductivity and high ammonia solubility and includes but is not limited to one or a combination of two or more of [BMIM][NTF2], [EMIM][Cu2Cl5], [BMIM][Cu2Cl5], choline chloride-urea ionic liquid, choline chloride-glycol ionic liquid and [Et3NH][HSO4]; The luminophore is a luminescent probe, which has electrochemiluminescence performance and includes but is not limited to one of Ru(bpy)3Cl2, Ir(ppy)3, Os(bpy)3Cl2 and lanthanide complex; The binder is a polymer with high molecular chain segments and bonding effect, including but not limited to one or more than two combinations of polyvinylidene fluoride, PAA, PTFE, PAN, PEDOT:PSS, PMMA, and PVA.

[0007] The solid-state electrolyte for ammonia detection, wherein the raw material of the solid-state electrolyte for ammonia detection further comprises a solvent; 0.1-5 mL of the solvent is added per 500 muL of the second electrolyte; The solvent is one or more than two combinations of N,N-dimethylacetamide, N,N-dimethylformamide, and acetonitrile.

[0008] Within the above dosage range, the formulation ratio is different, and the prepared solid-state electrolyte for ammonia detection can be a gel semi-solid or a full solid, which is collectively referred to as a solid in the present application.

[0009] The solid-state electrolyte for ammonia detection provided by the present application can realize ppb-level high sensitivity, wide linear response range, and low detection limit of NH3 selective detection at room temperature for the electrochemiluminescence sensor for detecting ammonia.

[0010] A preparation method of the solid-state electrolyte for ammonia detection as described above, comprising the following steps: The second electrolyte and the solvent are uniformly mixed, and the luminescent substance is added; After the luminescent substance is dissolved, stirring is performed until complete dispersion, and an electrolyte solution is prepared; The electrolyte solution is dried to prepare the solid-state electrolyte for ammonia detection; When the raw material comprises the first electrolyte, the first electrolyte is added to the solvent together with the second electrolyte; When the raw material comprises the binder, the binder is added after the luminescent substance is dissolved; The drying temperature is 40-80 DEG C, and the drying time is 0.5-8 h.

[0011] An electrochemiluminescence sensor for detecting ammonia, wherein the electrochemiluminescence sensor for detecting ammonia comprises a screen-printed electrode and the solid-state electrolyte for ammonia detection as described above; The screen-printed electrode comprises a working electrode, a counter electrode, and a reference electrode; The solid-state electrolyte for ammonia detection covers the surfaces of the working electrode, the counter electrode, and the reference electrode of the screen-printed electrode.

[0012] The electrochemiluminescence sensor for ammonia detection disclosed in this application has a solid electrolyte that completely covers the working electrode, counter electrode, and reference electrode of a screen-printed electrode. Ammonia sensing can be achieved through cyclic voltammetry and potentiostatic-luminescence technology, realizing highly sensitive and selective ammonia detection at the ppb level.

[0013] The electrochemiluminescence sensor for detecting ammonia gas, wherein a SWCNT sensing layer is further disposed between the working electrode and the solid electrolyte for ammonia gas detection; The SWCNT sensing layer is formed by heating and curing an SWCNT dispersion. The SWCNT dispersion was prepared by dispersing single-walled carbon nanotubes in anhydrous ethanol solution.

[0014] A method for preparing an electrochemiluminescence sensor for detecting ammonia as described above, comprising the following steps: The second electrolyte and the solvent are mixed evenly, and the luminescent material is added; After the luminescent material dissolves, it is stirred until completely dispersed to prepare an electrolyte solution; The electrolyte solution is drop-coated onto the surface of the screen-printed electrode, uniformly covering the surfaces of the working electrode, counter electrode, and reference electrode of the screen-printed electrode. The screen-printed electrode coated with the electrolyte solution is dried to prepare the screen-printed electrode having the solid electrolyte for ammonia detection as described above, i.e., the electrochemiluminescence sensor for ammonia detection. When the raw material includes the first electrolyte, the first electrolyte and the second electrolyte are added together to the solvent; When the raw materials include the binder, the binder is added after the luminescent material has dissolved; The drying temperature is 40-80℃, and the drying time is 0.5-8 h.

[0015] The method for preparing an electrochemiluminescence sensor for detecting ammonia, prior to the step of drop-coating the electrolyte solution onto the surface of a screen-printed electrode, further includes the following steps: Single-walled carbon nanotubes were dispersed in anhydrous ethanol solution to obtain SWCNT dispersion; The SWCNT dispersion is drop-coated onto the working electrode of the screen-printed electrode and then heated to cure, forming an SWCNT sensing layer. The concentration range of the SWCNT dispersion is 0.1-2 mg / mL; 10-50 μL of the SWCNT dispersion is dropped onto each square centimeter of the working electrode; During the heating and curing process, the heating temperature range is 40-80℃, and the heating time range is 5-30 minutes.

[0016] The method for preparing the electrochemiluminescence sensor for detecting ammonia, wherein the concentration range of the SWCNT dispersion is 1 mg / mL; 40 μL of the SWCNT dispersion was drop-coated onto each square centimeter of the working electrode; During the heat curing process, the heating temperature is 50°C and the heating time is 10 min. In the step of drying the screen-printed electrode coated with the electrolyte solution, the drying temperature is 50°C and the drying time is 1 hour. In the step of drop-coating the electrolyte solution onto the surface of the screen-printed electrode, 45 μL of the electrolyte solution is drop-coated per square centimeter of electrode. The first electrolyte is Nafion, the second electrolyte is [BMIM][NTF2], the luminescent material is made from Ru(bpy)3Cl2·6H2O, and the binder is polyvinylidene fluoride; The solvent is N,N-dimethylacetamide; The volume ratio between Nafion and [BMIM][NTF2] is 1:1, and the mass ratio between Ru(bpy)3Cl2·6H2O and polyvinylidene fluoride is 1:25; 10 mg of Ru(bpy)3Cl2·6H2O is added for every 500 μL of [BMIM][NTF2]. For every 500 μL of [BMIM][NTF2], add 4 mL of the N,N-dimethylacetamide.

[0017] A method for detecting ammonia, wherein the method employs an electrochemiluminescence sensor for detecting ammonia as described above, and performs sensing detection by cyclic voltammetry or potentiostatic-luminescence technology.

[0018] The method for detecting ammonia, wherein when sensing is performed using cyclic voltammetry, the method for detecting ammonia includes the following steps: A cyclic voltage of 0-1.6 V was applied to detect the ammonia content in the test gas at room temperature. A filter with a wavelength of 580-640 nm was used to collect the luminescence signal generated by the electrochemiluminescence sensor used for detecting ammonia. When sensing and detecting ammonia using potentiostatic-luminescence technology, the detection method includes the following steps: A constant luminescence potential is applied, and the ammonia content in the test gas is detected at room temperature. A filter with a wavelength of 580-640 nm is used to collect the luminescence signal generated by the electrochemiluminescence sensor used to detect ammonia. The parameters are set as follows: voltage is set to 1.3-1.5 V.

[0019] Beneficial effects: The electrochemiluminescence sensor for detecting ammonia in this application uses NH3 as a co-reactant and Ru(bpy)3 as the reactant. 2+ As the luminescent group, single-walled carbon nanotubes serve as the working electrode catalytic layer, with Nafion / IL / PVDF / Ru(bpy)3 as the luminescent group. 2+ This solid electrolyte is used for ammonia detection. It completely covers the working electrode, counter electrode, and reference electrode of the screen-printed electrode. Ammonia can be sensed by cyclic voltammetry and potentiostatic-luminescence technology, achieving high sensitivity and high selectivity of ammonia detection at the ppb level. Attached Figure Description

[0020] Figure 1 This is a schematic flowchart illustrating the preparation method of the electrochemiluminescence sensor for detecting ammonia according to this application.

[0021] Figure 2 This is a comparison of the ECL response curves of the electrochemiluminescence sensor for detecting ammonia in Example 1 of this application to different concentrations (1 ppm - 20 ppm) of NH3.

[0022] Figure 3 This is a graph showing the ECL response of the electrochemiluminescence sensor for detecting ammonia in Example 1 of this application to different concentrations (1 ppm - 20 ppm) of NH3.

[0023] Figure 4 This is a comparison of the ECL response curves of the electrochemiluminescence sensor for detecting ammonia in Example 2 of this application to different concentrations (5 ppm - 25 ppm) of NH3.

[0024] Figure 5 This is a graph showing the ECL response of the electrochemiluminescence sensor for detecting ammonia in Example 2 of this application to different concentrations (5 ppm - 25 ppm) of NH3.

[0025] Figure 6 This is a comparison of the ECL response curves of the electrochemiluminescence sensor for detecting ammonia in Example 3 of this application to different concentrations (500 ppb - 25 ppm) of NH3.

[0026] Figure 7 This is a graph showing the ECL response of the electrochemiluminescence sensor for detecting ammonia in Example 3 of this application to different concentrations (500 ppb - 25 ppm) of NH3.

[0027] Figure 8 This is a comparison of the ECL response curves of the electrochemiluminescence sensor for detecting ammonia in Example 4 of this application to 25 ppm of NH3, H2S and NO.

[0028] Figure 9 This is a graph showing the selectivity of the electrochemiluminescence sensor for detecting ammonia in Example 4 of this application for 25 ppm of NH3, H2S and NO. Detailed Implementation

[0029] This application provides a solid electrolyte for ammonia detection, an electrochemiluminescence sensor, and a preparation and detection method thereof. To make the objectives, technical solutions, and effects of this application clearer and more explicit, the following provides further detailed description. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0030] This application provides a solid electrolyte for ammonia detection, the raw materials of which include a second electrolyte, a luminescent material, an optional first electrolyte, and an optional binder; The volume ratio between the first electrolyte and the second electrolyte is 0-50:1-50; The mass ratio between the luminescent material and the binder is 0.1-100:0-2500; For every 100-5000 μL of the second electrolyte, add 1-1000 mg of luminescent material.

[0031] In this application, the second electrolyte and the luminescent material are essential raw materials, while the first electrolyte and the binder are optional raw materials. Therefore, the amount of the first electrolyte and the binder can be 0.

[0032] When the raw material of the solid electrolyte used for ammonia detection includes a second electrolyte, preferably, the volume ratio between the first electrolyte and the second electrolyte is 0.1-50:1-50.

[0033] When the raw materials of the solid electrolyte used for ammonia detection include luminescent material, preferably, the mass ratio between the luminescent material and the binder is 0.1-100:1-2500.

[0034] This application provides a method for preparing a solid electrolyte for ammonia detection, comprising the following steps: The second electrolyte and the solvent are mixed evenly, and the luminescent material is added; After the luminescent material dissolves, it is stirred until completely dispersed to prepare an electrolyte solution; The electrolyte solution was dried to prepare a solid electrolyte for ammonia detection. When the raw material includes the first electrolyte, the first electrolyte and the second electrolyte are added together to the solvent; When the raw materials include the binder, the binder is added after the luminescent material has dissolved.

[0035] The solid electrolyte for ammonia detection provided in this application enables selective NH3 detection at room temperature with ppb-level high sensitivity, wide linear response range, and low detection limit for electrochemiluminescence sensors used for ammonia detection. Therefore, based on this solid electrolyte for ammonia detection, this application also provides an electrochemiluminescence sensor for ammonia detection and its preparation method.

[0036] Specifically, this application provides a method for preparing an electrochemiluminescence sensor for detecting ammonia, the process of which is as follows: Figure 1 As shown, it includes the following steps: Step 1: Fabrication of SWCNT sensing layer 2 (this step can also be omitted).

[0037] Single-walled carbon nanotubes (SWCNTs) were dispersed in anhydrous ethanol solution to obtain an SWCNT dispersion. The SWCNT dispersion was drop-coated onto the working electrode of the screen-printed electrode 1 and then heated to cure, forming the SWCNT sensing layer 2.

[0038] Specifically, the concentration range of the SWCNT dispersion can be 0.1-2 mg / mL. In the embodiments of this application, the concentration of the SWCNT dispersion is 1 mg / mL. The concentration range of 0.1-2 mg / mL for the SWCNT dispersion is an optimal range derived from experimental verification and technical optimization, and has the following significant technical effects and advantages: 1. Avoiding dispersion defects: When the concentration is below 0.1 mg / mL, the SWCNT content in the SWCNT dispersion is too low, making it difficult to form a uniform dispersion system, resulting in low subsequent processing efficiency and insufficient product performance; while when the concentration is above 2 mg / mL, SWCNT is prone to agglomeration, resulting in decreased dispersion stability and increased viscosity, which is not conducive to process operation. Therefore, using the above concentration range for the SWCNT dispersion can effectively avoid the above defects. 2. Optimizing performance and cost: This concentration range can provide sufficient nanotube content to meet the electrocatalytic performance requirements while ensuring good dispersion of SWCNT, and at the same time avoids the excessive use of expensive materials, achieving a balance between performance and cost. 3. Strong process adaptability: Within this concentration range, the SWCNT dispersion exhibits moderate fluidity and stability, making it suitable for various processing techniques such as spraying, spin coating, and dipping, thus enhancing the flexibility and practicality of its application. 4. Verification through examples: The examples in this application use a typical concentration of 1 mg / mL to further verify the excellent performance of the SWCNT dispersion within this concentration range, fully demonstrating the technical feasibility and advancement of this concentration range.

[0039] During the heat curing process, the heating temperature range can be 40-80℃, and the heating time range can be 5-30 minutes. Heat curing strengthens the bond between the SWCNT sensing layer 2 and the working electrode. This temperature and time range comprehensively considers curing efficiency, interfacial bonding strength, and material thermal stability, avoiding the problems of insufficient curing at low temperatures and material damage at high temperatures. Preferably, in the embodiments of this application, the heat curing process is carried out at 50℃ for 10 minutes. This condition ensures a strong bond between the SWCNT sensing layer 2 and the working electrode while maximizing the preservation of the excellent electrical properties of SWCNT. The heat curing process of this application is simple, efficient, and applicable to various substrate materials.

[0040] In this application, the amount of SWCNT dispersion dropped is related to the working electrode area, and the dropping amount is 10-50 μL / cm², meaning 10-50 μL of SWCNT dispersion is used per square centimeter of working electrode. This range ensures the uniformity and coverage of the coating, optimizing the construction of the conductive network and electrochemical performance. In this embodiment, the working electrode area is approximately 0.125 square centimeters, and the dropping amount of SWCNT dispersion is 5 μL, calculated to be 40 μL of SWCNT dispersion per square centimeter of electrode. This amount further balances the uniformity, conductivity, and mechanical stability of the coating.

[0041] The screen printing electrode 1 includes a working electrode (WE), a counter electrode (CE), and a reference electrode (RE), wherein the working electrode and the counter electrode are made of carbon, and the reference electrode is made of Ag / AgCl.

[0042] Because Ru(bpy)3 2+ and Ru(bpy)3 3+ The electrochemical redox process can occur normally in cyclic voltammetry tests at 1-1.6V, therefore, the preparation of the SWCNT sensing layer 2 is not a necessary step. SWCNT is a good catalyst, and adding the SWCNT sensing layer 2 to the working electrode can further improve the catalytic efficiency; therefore, this step is the preferred option.

[0043] Step 2: Nafion / IL / PVDF / Ru(bpy)3 2+ Preparation of solid electrolyte 3 for ammonia detection.

[0044] Nafion (perfluorosulfonic acid polymer), [BMIM][NTF2] (1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt) and N,N-dimethylacetamide (DMA) were mixed evenly, and Ru(bpy)3Cl2·6H2O (terpyridine ruthenium chloride hexahydrate) was added. After Ru(bpy)3Cl2·6H2O dissolves, add polyvinylidene fluoride (PVDF) and stir until completely dispersed. This completes the preparation of the electrolyte solution, yielding the electrolyte solution Nafion / IL / PVDF / Ru(bpy)3. 2+ ; The electrolyte solution is drop-coated onto the surface of the screen-printed electrode 1, uniformly covering the CE, RE and WE surfaces of the screen-printed electrode 1; The screen-printed electrode 1, coated with the electrolyte solution, is dried or vacuum-dried, and the Nafion / IL / PVDF / Ru(bpy)3 is completed by phase inversion. 2+Preparation of solid electrolyte 3 for ammonia detection: A Nafion / IL / PVDF / Ru(bpy)3 solution was prepared. 2+ The screen-printed electrode 1 of the solid electrolyte 3 for ammonia detection is the electrochemiluminescence sensor for ammonia detection in this application.

[0045] Specifically, the volume ratio between the first electrolyte and the second electrolyte is 0-50:1-50; the mass ratio between the luminescent material and the binder is 0.1-100:0-2500; and 1-1000 mg of luminescent material is added for every 100-5000 μL of the second electrolyte. This ratio range ensures the full utilization of the functions of each component and optimizes the ionic conductivity, mechanical strength, electrochemical activity, and film-forming properties of the system. In the embodiments of this application, the volume ratio between Nafion and [BMIM][NTF2] is 1:1, the mass ratio between Ru(bpy)3Cl2·6H2O and polyvinylidene fluoride is 1:25, and 10 mg of Ru(bpy)3Cl2·6H2O is added for every 500 μL of [BMIM][NTF2]. This ratio further balances the effects of each component and improves the uniformity and stability of the film. Nafion and [BMIM][NTF2] are the electrolyte components, PVDF is the binder, Nafion also acts as a binder, Ru(bpy)3Cl2·6H2O is the luminescent material, and DMA is the solvent.

[0046] In this application, Nafion is used as the first electrolyte component, which exhibits good proton conductivity and chemical stability. However, those skilled in the art will understand that other electrolyte materials can be used as substitutes without departing from the core concept of this application, such as, but not limited to, SPEEK, PBI, heteropolyacids, Nafion, or inorganic composite membranes. These substitute materials can achieve the same technical effects as this application and are all within the scope of protection of this application.

[0047] In this application, [BMIM][NTF2] is used as the second electrolyte component, which has good ionic conductivity and ammonia solubility. However, those skilled in the art will understand that other electrolyte materials can be used as substitutes without departing from the core concept of this application, such as, but not limited to: [EMIM][Cu2Cl5] (1-ethyl-3-methylimidazolium pentachlorodicopperate), [BMIM][Cu2Cl5] (1-butyl-3-methylimidazolium pentachlorodicopperate), choline chloride / urea (ChCl / Urea, typically a molar ratio of 1:2), choline chloride / ethylene glycol (ChCl / EG, typically a molar ratio of 1:2), and [Et3NH][HSO4] (triethylamine hydrogen sulfate). These substitute materials can also achieve the technical effects of this application and are all within the scope of protection of this application.

[0048] In this application, Ru(bpy)3Cl2 is used as the luminescent material, which exhibits high luminescence efficiency and good stability. However, those skilled in the art will understand that other luminescent materials can be used as substitutes without departing from the core concept of this application, such as, but not limited to, Ir(ppy)3, Os(bpy)3Cl2, and lanthanide complexes. These substitute materials can achieve the same technical effects as this application and are all within the scope of protection of this application.

[0049] In this application, polyvinylidene fluoride (PVDF) is used as the binder, which possesses excellent bonding properties and electrochemical stability. However, those skilled in the art will understand that other binder materials can be used as substitutes without departing from the core concept of this application, such as, but not limited to, PAA, PTFE, PAN, PEDOT:PSS, PMMA, PVA, etc. These substitute materials can achieve the same technical effects as this application and are all within the scope of protection of this application.

[0050] In this application, a combination of Nafion, [BMIM][NTF2], Ru(bpy)3Cl2·6H2O, and polyvinylidene fluoride (PVDF) is used to form a multifunctional composite material with synergistic effects. Nafion provides a proton conduction channel, [BMIM][NTF2] acts as an ionic liquid to enhance conductivity, electrochemical window, and ammonia solubility, Ru(bpy)3Cl2·6H2O imparts excellent luminescent properties and sensing stability, while PVDF ensures the material's mechanical strength and film-forming properties. This combination not only significantly improves electrochemical performance but also enhances the sensor's stability and lifespan.

[0051] N,N-Dimethylacetamide is used as the solvent. The amount of N,N-dimethylacetamide used ranges from 0.1 to 5 mL per 500 μL of [BMIM][NTF2]. This ratio has been optimized to ensure sufficient dissolution and dispersion of [BMIM][NTF2] and Nafion, while also forming a uniform, dense film with good mechanical strength. Too low a ratio will result in insufficient dissolution, affecting film quality; too high a ratio will result in an excessively thin film with reduced mechanical strength. In the embodiments of this application, 4 mL of N,N-dimethylacetamide is added per 500 μL of [BMIM][NTF2], further optimizing flowability and film uniformity, making it suitable for large-area processes, and significantly improving the stability and electrochemical performance of sensor fabrication.

[0052] In this application, N,N-dimethylacetamide is used as a solvent, which is a good solvent. However, those skilled in the art will understand that other solvents can be used as substitutes without departing from the core concept of this application, such as, but not limited to, N,N-dimethylformamide, acetonitrile, etc. These substitute materials can also achieve the technical effects of this application and are all within the protection scope of this application. In the step, through drying treatment, the Nafion / IL / PVDF / Ru(bpy)3 is converted using a phase inversion method. 2+ The electrolyte solution is converted to Nafion / IL / PVDF / Ru(bpy)3 2+ Solid electrolyte 3. The drying process involves drying at a temperature of 40-80℃ for 0.5-8 hours. This range is optimized to ensure sufficient solvent evaporation while promoting polymer chain rearrangement and phase separation, resulting in a uniform and dense solid electrolyte membrane. Too low a temperature leads to slow solvent evaporation and insufficient membrane solidification; too high a temperature may cause rapid solvent evaporation, forming pinholes or bubbles, or even thermal degradation of the material. Too short a drying time results in solvent residue, affecting electrochemical performance; too long a time reduces production efficiency. In the embodiments of this application, the drying process involves drying at 50℃ for 1 hour, further optimizing the uniformity and mechanical strength of the membrane structure while maintaining process efficiency, making it suitable for large-scale industrial production.

[0053] In this step, the amount of electrolyte solution dropped depends on the electrode area, ranging from 10-100 μL / cm², meaning 10-100 μL of electrolyte solution is dropped per square centimeter of electrode. This range is optimized to ensure that the electrolyte membrane completely covers the electrode surface, forming a uniform and dense film, while also providing sufficient ion conduction channels to ensure the device's sensitivity, response speed, and stability. If the dropping amount is too low, the film will be too thin, failing to completely cover the electrode and affecting electrochemical and sensing performance; if the dropping amount is too high, the film will be too thick, reducing ion conductivity and causing uneven solvent evaporation, affecting film uniformity. In this embodiment, the electrode area is approximately 0.333 square centimeters (here, the electrode area refers to the area of ​​the test region, covering the working electrode, counter electrode, and reference electrode; the test region is as follows). Figure 1 The solid electrolyte 3 shown is used for ammonia detection. The amount of electrolyte solution dropped is 15 μL, which is calculated to be 45 μL of electrolyte solution dropped per square centimeter of electrode. This amount can further optimize the uniformity, electrochemical and sensing performance of the film layer, while taking into account process efficiency and material utilization, making it suitable for large-scale industrial production.

[0054] Furthermore, this application also provides an electrochemiluminescence sensor for detecting ammonia, which is prepared using the above-described preparation method for an electrochemiluminescence sensor for detecting ammonia.

[0055] The electrochemiluminescence sensor for detecting ammonia in the embodiments of this application uses NH3 as a co-reactant and Ru(bpy)3 as a reactant. 2+ As the luminescent group, single-walled carbon nanotubes serve as the working electrode catalytic layer, with Nafion / IL / PVDF / Ru(bpy)3 as the luminescent group. 2+ As a solid electrolyte, the solid electrolyte completely covers the working electrode, counter electrode, and reference electrode of the screen-printed electrode. Ammonia gas sensing can be performed by cyclic voltammetry and potentiostatic-luminescence technology, achieving highly sensitive and selective ammonia gas detection at the ppb level.

[0056] Furthermore, this application also provides an ammonia detection method based on the electrochemiluminescence sensor for detecting ammonia, which is divided into two types: cyclic voltammetry and potentiostatic-luminescence technology.

[0057] Specifically, an ammonia detection method based on the electrochemiluminescence sensor for detecting ammonia gas according to this application, which performs sensing detection by cyclic voltammetry, includes the following steps: Choose nitrogen or air as the background gas. At room temperature, introduce the background gas into the gas chamber to purge impurities from the gas chamber and gas path, and then introduce the gas to be tested. A cyclic voltage of 0-1.6 V was applied, and the ammonia content in the test gas was detected at room temperature. The luminescence signal generated by the electrochemiluminescence sensor used for ammonia detection was collected. Other parameters can be set as follows: scan rate 50-300 mV / s, sampling interval 0.05-0.5 V, and sampling rate 0.01-1 s.

[0058] Using the optimized parameter range described above, Ru(bpy)3 can be effectively covered. 2+ The oxidation peak potential is determined to ensure detection sensitivity and selectivity. The selection of the scan rate balances detection efficiency and signal quality; the setting of the sampling interval and sampling rate ensures the accuracy and real-time performance of data acquisition. In the embodiments of this application, typical parameter combinations are used to further optimize detection performance, making it suitable for various application scenarios and enhancing the practicality of this application.

[0059] The flow rates of the background gas and the gas to be tested can be set to 100-1000 mL / min.

[0060] When performing sensor detection using cyclic voltammetry, the process of introducing the test gas involves continuously introducing the test gas until the cyclic voltammetry test is completed, at which point the introduction of the test gas stops. When it is necessary to test the next test gas, background gas is first introduced until the residual test gas in the chamber is exhausted, and then the next test gas is introduced to start the cyclic voltammetry test for the next test gas.

[0061] Preferably, the flow rates of the background gas and the gas to be tested are set to 100 mL / min, the scan rate is set to 100 mV / s, the sampling interval is set to 0.05 V, and the sampling rate is set to 0.5 s. This gas flow rate setting ensures sufficient contact between the gas to be tested and the electrode; the optimization of this scan rate and sampling parameters balances detection efficiency and data accuracy.

[0062] Specifically, an ammonia detection method based on the electrochemiluminescence sensor for detecting ammonia according to this application, which uses potentiostatic-luminescence technology for sensing detection, includes the following steps: Choose nitrogen or air as the background gas. At room temperature, introduce the background gas into the gas chamber to purge impurities from the gas chamber and gas path, and then introduce the gas to be tested. A constant luminescence potential is applied, and the ammonia content in the test gas is detected at room temperature. The luminescence signal generated by the electrochemiluminescence sensor used for ammonia detection is collected. The parameters are set as follows: voltage can be set to 1.3-1.5 V. Other parameters can be set as follows: sampling interval to 0.05-0.5 s, sampling rate to 0.01-1 s. This voltage setting covers Ru(bpy)3. 2+ The settings for the oxidation peak potential, sampling interval, and sampling rate ensure the accuracy and real-time performance of data acquisition.

[0063] When using potentiostatic emission technology for sensing, the gas to be tested is introduced until the emission signal stabilizes, then the gas introduction is stopped. When testing the next gas, background gas is introduced first until the residual gas from the previous gas in the chamber is exhausted, and then the next gas is introduced.

[0064] The flow rates of the background gas and the gas to be tested can be set to 100-1000 mL / min.

[0065] Preferably, the flow rates of the background gas and the gas to be tested are set to 100 mL / min, the voltage is set to 1.35 V, the sampling interval is set to 0.5 s, and the sampling rate is set to 0.5 s. Performing potentiostatic testing at the oxidation peak potential ensures the maximum Ru(bpy)3 concentration. 2+ The oxidation rate is optimized to ensure the sensor's sensitivity; the optimization of sampling parameters balances detection efficiency and data accuracy.

[0066] Preferably, in the above ammonia detection method, when detecting the ammonia content in the gas to be tested at room temperature, a filter with a wavelength of 580-640 nm is used to collect the luminescence signal (ECL signal) generated by the electrochemiluminescence sensor. Most preferably, a filter with a wavelength of 620 nm is used.

[0067] In this application, a filter is used to select a wavelength that matches the characteristic optical response of ammonia or its indicator. Using a filter during gas detection can improve the signal-to-noise ratio and selectivity. Employing a 620 nm wavelength filter maximizes signal strength, significantly improves detection sensitivity, and effectively reduces optical interference in the environment. This preferred wavelength balances system performance and practical application requirements, enhancing the applicability of this application.

[0068] The technical solution of this application has the following advantages: 1. This application provides a novel electrochemiluminescence sensor for detecting ammonia, prepared by fabricating Nafion / IL / PVDF / Ru(bpy)3. 2+ Solid-state electrolyte enables selective detection of NH3 at ppb level with high sensitivity, wide linear response range and low detection limit at room temperature.

[0069] 2. This application provides a test method based on potentiostatic-luminescence technology applicable to the field of electrochemiluminescence gas sensing, which improves sensor performance through this innovative method.

[0070] The present application will be further described below through specific embodiments.

[0071] The sources and models of the main raw materials and components in the following embodiments are as follows: SWCNT: Mecklen, ≥95%; Outer diameter: <2 nm; Length: 5-30 μm; Screen printing electrode: Qingdao Botan, TC201; Nafion: DuPont (Chemours), D-520 (5 wt%); [BMIM][NTF2]: Inokai, 99% purity; PVDF: Inokai, average Mw ~400,000, powder; Ru(bpy)3Cl2·6H2O: Inokai, 98% purity.

[0072] Example 1 This embodiment prepares a material based on Nafion / IL / PVDF / Ru(bpy)3 2+ The specific steps of the solid electrolyte electrochemiluminescence sensor for detecting ammonia are as follows: Step (1): Fabrication of the SWCNT sensing layer 1 mg of SWCNT was dispersed in 1 mL of anhydrous ethanol solution to obtain a 1 mg / mL SWCNT solution. 5 μL of the SWCNT dispersion was drop-coated onto the WE of a screen-printed electrode (working and counter electrodes were carbon, and the reference electrode was Ag / AgCl). The screen-printed electrode with the SWCNT dispersion was heated at 50 °C for 10 min to solidify the sensing layer, enhancing the bonding between the sensing layer and the working electrode, thus completing the preparation of the SWCNT sensing layer.

[0073] Step (two): Nafion / IL / PVDF / Ru(bpy)3 2+ Preparation of solid electrolytes Mix 500 μL of Nafion, 500 μL of [BMIM][NTF2], and 4 mL of N,N-dimethylacetamide (DMA) thoroughly. Add 10 mg of Ru(bpy)3Cl2·6H2O and allow it to dissolve. Then add 0.25 g of polyvinylidene fluoride (PVDF) and stir until completely dispersed. This completes the preparation of the electrolyte solution. In this mixture, Nafion and [BMIM][NTF2] constitute the electrolyte, Nafion and PVDF act as binders, Ru(bpy)3Cl2·6H2O is the luminescent material, and DMA is the solvent.

[0074] Take 15 μL of the prepared electrolyte solution and drop it onto the surface of the screen-printed electrode, uniformly covering CE, RE, and WE with the SWCNT sensing layer. Dry the screen-printed electrode with the electrolyte solution at 50℃ for 1 h, and complete the Nafion / IL / PVDF / Ru(bpy)3 phase inversion process. 2+ The preparation of the solid electrolyte yielded the electrochemiluminescence sensor used for detecting ammonia in this embodiment.

[0075] The electrochemiluminescence sensor for detecting ammonia in this embodiment was tested using cyclic voltammetry.

[0076] The parameters are set as follows: voltage is 0~1.6 V, scan rate is 100 mV / s, sampling interval is 0.05 V, and sampling rate is 0.5 s.

[0077] Nitrogen was selected as the background gas. The background gas flow rate was set to 100 mL / min and introduced into the gas chamber. After purging impurities from the gas chamber and gas path at room temperature, different concentrations of NH3 (the analyte gas) were introduced at the same flow rate as the background gas. A cyclic voltage was applied, and the ammonia content in the analyte gas was detected at room temperature. A 620 nm wavelength filter was used to collect the emission signal (ECL signal) generated by the electrochemiluminescence sensor. The test results are as follows: Figures 2-3As shown in the diagram. The process of introducing different concentrations of NH3 involves continuously introducing a certain concentration of ammonia gas until the cyclic voltammetry test for that concentration is completed, and then starting the cyclic voltammetry test for the next concentration of ammonia. The different concentrations of NH3 are 0 ppm (nitrogen, N2), 1 ppm, 2.5 ppm, 5 ppm, 10 ppm, 15 ppm, and 20 ppm.

[0078] from Figures 2-3 As can be seen, based on Nafion / IL / PVDF / Ru(bpy)3 2+ The electrochemiluminescence sensor using a solid electrolyte for ammonia detection has a sensitivity of 194.9 ppm for NH3. -1 1 ppm NH3 was detected.

[0079] from Figure 3 As can be seen, the electrochemiluminescence sensor for detecting ammonia in this embodiment exhibits a linear correlation between the ECL response and the NH3 concentration in the concentration range of 0ppm-20ppm. The sensor can be used for highly sensitive and quantitative analysis of low-concentration NH3.

[0080] Example 2 This embodiment prepares a material based on Nafion / IL / Ru(bpy)3 2+ The electrochemiluminescence sensor used to detect ammonia gas follows these steps: Step (1): Fabrication of the SWCNT sensing layer 1 mg of SWCNT was dispersed in 1 mL of anhydrous ethanol solution to obtain a 1 mg / mL SWCNT solution. 5 μL of the SWCNT dispersion was drop-coated onto the WE of a screen-printed electrode (working and counter electrodes were carbon, and the reference electrode was Ag / AgCl). The screen-printed electrode with the SWCNT dispersion was heated at 50 °C for 10 min to solidify the sensing layer, enhancing the bonding between the sensing layer and the working electrode, thus completing the preparation of the SWCNT sensing layer.

[0081] Step (two): Nafion / IL / Ru(bpy)3 2+ Preparation of solid electrolytes Mix 500 μL of Nafion, 500 μL of [BMIM][NTF2], and 4 mL of N,N-dimethylacetamide (DMA) thoroughly. Add 10 mg of Ru(bpy)3Cl2·6H2O and stir until completely dissolved. This completes the preparation of the electrolyte solution. In this mixture, Nafion and [BMIM][NTF2] constitute the electrolyte, Nafion acts as a binder, Ru(bpy)3Cl2·6H2O is the luminescent substance, and DMA is the solvent.

[0082] Take 15 μL of the prepared electrolyte solution and drop it onto the surface of the screen-printed electrode, uniformly covering CE, RE, and WE with the SWCNT sensing layer. Dry the screen-printed electrode with the electrolyte solution at 50℃ for 1 h, and complete the Nafion / IL / Ru(bpy)3 reaction by phase inversion. 2+ A solid electrolyte was prepared to obtain the electrochemiluminescence sensor used for detecting ammonia in this embodiment.

[0083] The electrochemiluminescence sensor used in this embodiment for detecting ammonia was tested using cyclic voltammetry.

[0084] The parameters are set as follows: voltage is 0~1.6 V, scan rate is 100 mV / s, sampling interval is 0.05 V, and sampling rate is 0.5 s.

[0085] Nitrogen was selected as the background gas. The background gas flow rate was set to 100 mL / min and introduced into the gas chamber. After purging impurities from the gas chamber and gas path at room temperature, different concentrations of NH3 (the analyte gas) were introduced at the same flow rate as the background gas. A cyclic voltage was applied, and the ammonia content in the analyte gas was detected at room temperature. A 620 nm wavelength filter was used to collect the emission signal (ECL signal) generated by the electrochemiluminescence sensor. The test results are as follows: Figures 4-5 As shown in the diagram. The process of introducing different concentrations of NH3 involves continuously introducing a certain concentration of ammonia gas until the cyclic voltammetry test for that concentration is completed, and then starting the cyclic voltammetry test for the next concentration of ammonia. The concentrations of NH3 at different concentrations are 0 ppm (nitrogen, N2), 5 ppm, 10 ppm, 15 ppm, and 25 ppm.

[0086] from Figures 4-5 As can be seen, based on Nafion / IL / Ru(bpy)3 2+ The electrochemiluminescence sensor based on a solid electrolyte has a sensitivity of 114.0 ppm for detecting ammonia. -1 .

[0087] from Figure 5 It can be seen that, in the concentration range of 0ppm-25ppm, the electrochemiluminescence sensor for detecting ammonia in this embodiment shows a linear correlation between the ECL response and the NH3 concentration.

[0088] Example 3 This embodiment prepares a material based on Nafion / IL / Ru(bpy)3 2+ The specific steps of the solid electrolyte electrochemiluminescence sensor for detecting ammonia are as follows: Step (1): Nafion / IL / Ru(bpy)3 2+ Preparation of solid electrolytes Mix 500 μL of Nafion, 500 μL of [BMIM][NTF2], and 4 mL of N,N-dimethylacetamide (DMA) thoroughly. Add 10 mg of Ru(bpy)3Cl2·6H2O and stir until completely dissolved. This completes the preparation of the electrolyte solution. In this mixture, Nafion and [BMIM][NTF2] constitute the electrolyte, Nafion acts as a binder, Ru(bpy)3Cl2·6H2O is the luminescent substance, and DMA is the solvent.

[0089] Take 15 μL of the prepared electrolyte solution and drop it onto the surface of the screen-printed electrode, uniformly covering CE, RE, and WE with the SWCNT sensing layer. Dry the screen-printed electrode with the electrolyte solution at 50℃ for 1 h, and complete the Nafion / IL / Ru(bpy)3 reaction by phase inversion. 2+ Preparation of solid electrolytes.

[0090] The electrochemiluminescence sensor used in this embodiment for detecting ammonia was tested using potentiostatic-luminescence technology.

[0091] The parameters are set as follows: operating potential is 1.35 V, sampling interval is 0.5 s, and sampling rate is 0.5 s.

[0092] Nitrogen was selected as the background gas. At room temperature, the background gas was introduced into the gas chamber at a flow rate of 100 mL / min to purge impurities from the gas chamber and gas path. Testing was conducted at room temperature. Once the background signal stabilized, a specific concentration of NH3 (the analyte gas) was introduced at the same flow rate as the background gas until the luminescence signal stabilized. The analyte gas was then stopped, and the background gas was introduced until any residual analyte gas from the previous gas was purged from the gas chamber. The next concentration of analyte gas was then introduced. A 620 nm wavelength filter was used to collect the luminescence signal (ECL signal) generated by the electrochemiluminescence sensor. The ECL signal was recorded, and the test results are shown below. Figures 6-7 As shown in the figure. The concentrations of NH3 introduced were 25 ppm, 25 ppm, 25 ppm, 20 ppm, 15 ppm, 5 ppm, and 500 ppb, respectively.

[0093] from Figures 6-7 As can be seen, based on Nafion / IL / Ru(bpy)3 2+ An electrochemiluminescence sensor based on solid-state electrolytes for ammonia detection can detect NH3 from 500 ppb to 25 ppm and exhibits good linearity R. 2 =0.994, sensitivity is 9852.7 ppm -1 .

[0094] Example 4 This embodiment prepares a material based on Nafion / IL / PVDF / Ru(bpy)3 2+ Selectivity testing was performed on the solid electrolyte electrochemiluminescence sensor, and the preparation steps were the same as in Example 1.

[0095] In this embodiment, the selectivity of the electrochemiluminescence ammonia sensor is explained by comparing the ΔCount (Δluminescence intensity) of 25 ppm NO (nitric oxide), 25 ppm H2S (hydrogen sulfide), and 25 ppm NH3 (ammonia).

[0096] Specifically, the electrochemiluminescence sensor for detecting ammonia in this embodiment was tested using cyclic voltammetry.

[0097] The parameters are set as follows: voltage is 0~1.6 V, scan rate is 100 mV / s, sampling interval is 0.05 V, and sampling rate is 0.5 s.

[0098] Nitrogen (N2) was selected as the background gas. The background gas was introduced into the gas chamber at a flow rate of 100 mL / min. After purging impurities from the gas chamber and gas path at room temperature, 25 ppm NO, 25 ppm H2S, and 25 ppm NH3 were introduced at the same flow rates as the background gas. A cyclic voltage was applied, and the emission signal (ECL signal) generated by the electrochemiluminescence sensor was acquired using a 620 nm wavelength filter. The test results are as follows: Figures 8-9 As shown.

[0099] from Figures 8-9 As can be seen, based on Nafion / IL / PVDF / Ru(bpy)3 2+ The solid electrolyte electrochemiluminescence sensor exhibits good selectivity for NH3, while the ECL response of interfering gases is significantly lower than that of NH3.

[0100] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.

Claims

1. A solid electrolyte for ammonia detection, characterized in that, Its raw materials include a second electrolyte, a luminescent material, an optional first electrolyte, and an optional binder; The volume ratio between the first electrolyte and the second electrolyte is 0-50:1-50; The mass ratio of the luminescent material to the binder is 0.1-100:0-2500; 1-1000 mg of the luminescent substance is added for every 100-5000 μL of the second electrolyte; The first electrolyte includes, but is not limited to, one or more of SPEEK, PBI, heteropolyacids, Nafion, and inorganic composite membranes; The second electrolyte includes, but is not limited to, one or more combinations of [BMIM][NTF2], [EMIM][Cu2Cl5], [BMIM][Cu2Cl5], choline chloride-urea ionic liquid, choline chloride-ethylene glycol ionic liquid, and [Et3NH][HSO4]. The luminescent material includes, but is not limited to, one of Ru(bpy)3Cl2, Ir(ppy)3, Os(bpy)3Cl2, and lanthanide complexes; The adhesive includes, but is not limited to, one or a combination of two or more of polyvinylidene fluoride, PAA, PTFE, PAN, PEDOT:PSS, PMMA, and PVA.

2. The solid electrolyte for ammonia detection according to claim 1, characterized in that, The raw materials for the solid electrolyte used for ammonia detection also include solvents; For every 500 μL of the second electrolyte, add 0.1-5 mL of the solvent. The solvent includes, but is not limited to, one or a combination of two or more of N,N-dimethylacetamide, N,N-dimethylformamide, and acetonitrile.

3. A method for preparing a solid electrolyte for ammonia detection as described in any one of claims 1-2, characterized in that, Includes the following steps: The second electrolyte and the solvent are mixed evenly, and the luminescent material is added; After the luminescent material dissolves, it is stirred until completely dispersed to prepare an electrolyte solution; The electrolyte solution is dried to prepare the solid electrolyte for ammonia detection. When the raw material includes the first electrolyte, the first electrolyte and the second electrolyte are added together to the solvent; When the raw materials include the binder, the binder is added after the luminescent material has dissolved; The drying temperature is 40-80℃, and the drying time is 0.5-8 h.

4. An electrochemiluminescence sensor for detecting ammonia, characterized in that, The electrochemiluminescence sensor for detecting ammonia includes a screen-printed electrode and a solid electrolyte for ammonia detection as described in any one of claims 1-2; The screen-printed electrode includes a working electrode, a counter electrode, and a reference electrode; The solid electrolyte for ammonia detection covers the surfaces of the working electrode, the counter electrode, and the reference electrode of the screen-printed electrode.

5. The electrochemiluminescence sensor for detecting ammonia according to claim 4, characterized in that, A SWCNT sensing layer is also provided between the working electrode and the solid electrolyte for ammonia detection; The SWCNT sensing layer is formed by heating and curing an SWCNT dispersion. The SWCNT dispersion was prepared by dispersing single-walled carbon nanotubes in anhydrous ethanol solution.

6. A method for preparing an electrochemiluminescence sensor for detecting ammonia as described in any one of claims 4-5, characterized in that, Includes the following steps: The second electrolyte and the solvent are mixed evenly, and the luminescent material is added; After the luminescent material dissolves, it is stirred until completely dispersed to prepare an electrolyte solution; The electrolyte solution is drop-coated onto the surface of the screen-printed electrode, uniformly covering the surfaces of the working electrode, counter electrode, and reference electrode of the screen-printed electrode. The screen-printed electrode coated with the electrolyte solution is dried to prepare the screen-printed electrode having the solid electrolyte for ammonia detection as described in any one of claims 1-2, i.e. the electrochemiluminescence sensor for ammonia detection. When the raw material includes the first electrolyte, the first electrolyte and the second electrolyte are added together to the solvent; When the raw materials include the binder, the binder is added after the luminescent material has dissolved; The drying temperature is 40-80℃, and the drying time is 0.5-8 h.

7. The method for preparing the electrochemiluminescence sensor for detecting ammonia according to claim 6, characterized in that, Prior to the step of drop-coating the electrolyte solution onto the screen-printed electrode surface, the method for preparing the electrochemiluminescence sensor for detecting ammonia further includes the following steps: Single-walled carbon nanotubes were dispersed in anhydrous ethanol solution to obtain SWCNT dispersion; The SWCNT dispersion is drop-coated onto the working electrode of the screen-printed electrode and then heated to cure, forming an SWCNT sensing layer. The concentration range of the SWCNT dispersion is 0.1-2 mg / mL; 10-50 μL of the SWCNT dispersion is dropped onto each square centimeter of the working electrode; During the heating and curing process, the heating temperature range is 40-80℃, and the heating time range is 5-30 min.

8. The method for preparing the electrochemiluminescence sensor for detecting ammonia according to claim 7, characterized in that, The concentration range of the SWCNT dispersion is 1 mg / mL; 40 μL of the SWCNT dispersion was drop-coated onto each square centimeter of the working electrode; During the heat curing process, the heating temperature is 50°C and the heating time is 10 min. In the step of drying the screen-printed electrode coated with the electrolyte solution, the drying temperature is 50°C and the drying time is 1 hour. In the step of drop-coating the electrolyte solution onto the surface of the screen-printed electrode, 45 μL of the electrolyte solution is drop-coated per square centimeter of electrode. The first electrolyte is Nafion, the second electrolyte is [BMIM][NTF2], the luminescent material is made from Ru(bpy)3Cl2·6H2O, and the binder is polyvinylidene fluoride; The solvent is N,N-dimethylacetamide; The volume ratio between Nafion and [BMIM][NTF2] is 1:1, and the mass ratio between Ru(bpy)3Cl2·6H2O and polyvinylidene fluoride is 1:25; 10 mg of Ru(bpy)3Cl2·6H2O is added for every 500 μL of [BMIM][NTF2]. For every 500 μL of [BMIM][NTF2], add 4 mL of the N,N-dimethylacetamide.

9. A method for detecting ammonia, characterized in that, The detection method for ammonia gas employs the electrochemiluminescence sensor for ammonia gas detection as described in any one of claims 4-5, and performs sensing detection by cyclic voltammetry or potentiostatic-luminescence technology.

10. The detection method for ammonia according to claim 9, characterized in that, When using cyclic voltammetry for sensing detection, the detection method for ammonia includes the following steps: A cyclic voltage of 0-1.6 V was applied to detect the ammonia content in the test gas at room temperature. A filter with a wavelength of 580-640 nm was used to collect the luminescence signal generated by the electrochemiluminescence sensor used for detecting ammonia. When sensing and detecting ammonia using potentiostatic-luminescence technology, the detection method includes the following steps: A constant luminescence potential is applied to detect the ammonia content in the test gas at room temperature. A filter with a wavelength of 580-640 nm is used to collect the luminescence signal generated by the electrochemiluminescence sensor used to detect ammonia. The parameters are set as follows: voltage is set to 1.3-1.5 V.

Citation Information

Patent Citations

  • Ultrathin all-solid-state formaldehyde electrochemical gas sensor

    CN113588738A

  • Potential type passive NH3 sensor based on hydrogel solid electrolyte and preparation thereof

    CN118311116A

  • MEMS electrochemical gas sensor and processing method thereof

    CN119666941A

  • Novel electrochemiluminescence co-reactant, electrolyte solution and electrochemiluminescence system comprising same

    US20230365859A1

Cited By

  • PH electrochemical detection test paper and preparation method thereof

    CN122330214A

  • A pH electrochemical test paper and a preparation method thereof

    CN122330214B